Generating evidence for health policy in challenging settings: lessons learned from four prevention of mother-to-child transmission of HIV implementation research studies in Nigeria - Nadia A. Sam-Agudu; Muktar H. Aliyu; Olusegun A. Adeyemi; Frank Oronsaye; Bolanle Oyeledun; Amaka G. Ogidi; Echezona E. Ezeanolue (BMC, 2018)
Abstract Background Implementation research (IR) facilitates health systems strengthening and optimal patient outcomes by generating evidence for scale-up of efficacious strategies in context. Thus, difficulties in generating IR evidence, particularly in limited-resource settings with wide disease prevention and treatment gaps, need to be anticipated and addressed. Nigeria is a priority country for the prevention of mother-to-child transmission of HIV (PMTCT). This paper analyses the experiences of four PMTCT IR studies in Nigeria, and proffers solutions to major challenges encountered during implementation. Studies included and findings Multicentre PMTCT IR studies conducted in Nigeria during the Global Plan's assessment period (2011 to 2015) were included. Four studies were identified, namely The Baby Shower Trial, Optimizing PMTCT, MoMent and Lafiyan Jikin Mata. Major common challenges encountered were categorised as 'External' (beyond the control of study teams) and 'Internal' (amenable to rectification by study teams). External challenges included healthcare worker strikes and turnover, acts and threats of ethnic and political violence and terrorism, and multiplicity of required local ethical reviews. Internal challenges included limited research capacity among study staff, research staff turnover and travel restrictions hindering study site visits. Deliberate research capacity-building was provided to study staff through multiple opportunities before and during study implementation. Post-study employment opportunities and pathways for further research career-building are suggested as incentives for study staff retention. Engagement of study community-resident personnel minimised research staff turnover in violence-prone areas. Conclusions The IR environment in Nigeria is extremely diverse and challenging, yet, with local experience and anticipatory planning, innovative solutions can be implemented to modulate internal challenges. Issues still remain with healthcare worker strikes and often unpredictable insecurity. There is a dire need for cooperation between institutional review boards across Nigeria in order to minimise the multiplicity of reviews for multicentre studies. External challenges need to be addressed by high-level stakeholders, given Nigeria's crucial regional and global position in the fight against the HIV epidemic.